Pengkonturan garis sempadan wajah manusia menggunakan model kontur aktif - Shahlan, Haryati (2005)
The development of this application is especially to contour the human frontal face boundary from colour or grayscale level image. Facial boundary contoured includes facial features like forehead, eyebrows, eyes, nose, cheek, mouth and chin. The contouring process determine by adapting Active Contour Model or known as Snake Deformable. The application allows users to choose two vector field named as Standard Vector Field (SVF) and Gradient Vector Flow (GVF). These two vector field gives differential contour output form. GVF can improve the capture range of the image force that suffers by SVF. Thereby, it can reduce number of snake iterations. However, the result of SVF contour is much better than GVF. Users also allowed setting the initial active contour and key in active contour parametric value such as tension force (a), rigidity force (ÃŸ), step size (?), external force weight (?), maximum distance point (Dmax), minimum distance point (Dmin) and number of iterations.